Effects of Ultramicronized Palmitoylethanolamide on Mitochondrial Bioenergetics, Cerebral Metabolism, and Glutamatergic Transmission: An Integrated Approach in a Triple Transgenic Mouse Model of Alzheimer's Disease - Bellanti, Francesco; Bukke, Vidyasagar Naik; Moola, Archana; Villani, Rosanna; Scuderi, Caterina; Steardo, Luca; Palombelli, Gianmauro; Canese, Rossella; Beggiato, Sarah; Altamura, Mario; Vendemiale, Gianluigi; Serviddio, Gaetano; et al. (Frontiers in Aging Neuroscience, 2022)
The therapeutic potential of ultramicronized palmitoylethanolamide (um-PEA) was investigated in young (6-month-old) and adult (12-month-old) 3×Tg-AD mice, which received um-PEA for 3 months via a subcutaneous delivery system. Mitochondrial bioenergetics, ATP homeostasis and magnetic resonance imaging/magnetic resonance spectroscopy were evaluated in the frontal cortex (FC) and hippocampus (HIPP) at the end of um-PEA treatment. Glutamate release was investigated by in vivo microdialysis in the ventral HIPP (vHIPP). We demonstrated that chronic um-PEA treatment ameliorates the decrease in the complex-I respiration rate and the FoF1-ATPase (complex V) activity, as well as ATP content depletion in the cortical mitochondria. Differently, the impairment in mitochondrial bioenergetics and in the release of glutamate after depolarization were not ameliorated by um-PEA treatment in the HIPP of both young and adult 3×Tg-AD mice. Moreover, progressive age- and pathology-related changes were observed in the cortical and hippocampal metabolism that closely mimic the alterations observed in the human AD brain; these metabolic alterations were not affected by chronic um-PEA treatment. These findings confirm that the HIPP is the most affected area by AD-like pathology and demonstrate that um-PEA counteracts mitochondrial dysfunctions and helps rescue brain energy metabolism in the FC, but not in the HIPP.